In vitro propagation of 'Echo' cultivars of Eustoma grandiflorum (Raf.) Shinn. - Ördögh, M.; Jámbor-Benczúr, E.; Tilly Mándy, A. (International Journal of Horticultural Science, 2005)
Eustoma grandiflorum (Raf.) Shinn. 'Echo' Fl cultivars ('Echo White', 'Echo Rose', 'Echo Blue', 'Echo Blue Picotee') were used and multiplication of shoots was evaluated on Murashige and Skoog (1962) basal medium with 11 g/1 agar-agar and 20 g/1 sucrose. To test the effect of BA different concentrations were added: 0.10, 0.25 mg/1 and a culture medium without BA. Differentiation of roots was examined on Jámbor-Benczúr and Marta (1990) basal medium with the same concentration of agar-agar and sucrose. To examine the effect on rooting, various concentrations of NAA were used: 0.5, 1.0, 2.0, 3.0 mg/l. The pH was adjusted to 5.6 in every case using KOH. We studied the after-effect of different concentrations of BA during the acclimatisation. During the multiplication, the cultivar 'Echo White' formed the most shoots and the smallest leaves on the medium with 0.10 mg/1 BA. Fortunately, in the case of this cultivar, the number of shoots was reduced and the length of leaves was increased succesfully on the medium without BA. The other three cultivars developed the longest leaves on the medium containing 0.10 mg/1 BA. Sometimes not only shoot regeneration but spontaneous rooting was observed during the multiplication. Examining the rooting, the highest percent of roots was found on the medium with 1.0 mg/1 NAA, and the cultivar 'Echo Rose' formed the most roots on this medium. Higher concentration (2.0 and 3.0 mg/1) of NAA already reduced the number of roots in all of the cultivars. During the acclimatisation, the percentage of survival was 76.3% and the tallest plants with the longest leaves were found on the multiplication medium with 0.25 mg/1 BA. 'Echo Blue Picotee' gave the best results with the tallest pieces and longest leaves on this medium.